Discovery and Characterization of a Novel MASTL Inhibitor MKI-2 Targeting MASTL-PP2A in Breast Cancer Cells and Oocytes - Minsung Kang; Chijung Kim; Jiyeon Leem; Ye-hyun Kim; Young-ju Kwon; Yi Na Yoon; Chong Hak Chae; Jiyeon Ahn; Kwan-Young Jung; Jeong Su Oh; Jae-Sung Kim (MDPI AG, 2021)
Although microtubule-associated serine/threonine kinase-like (MASTL) is a promising target for selective anticancer treatment, MASTL inhibitors with nano range potency and antitumor efficacy have not been reported. Here, we report a novel potent and selective MASTL inhibitor MASTL kinase inhibitor-2 (MKI-2) identified in silico through a drug discovery program. Our data showed that MKI-2 inhibited recombinant MASTL activity and cellular MASTL activity with IC50 values of 37.44 nM and 142.7 nM, respectively, in breast cancer cells. In addition, MKI-2 inhibited MASTL kinase rather than other AGC kinases, such as ROCK1, AKT1, PKACα, and p70S6K. Furthermore, MKI-2 exerted various antitumor activities by inducing mitotic catastrophe resulting from the modulation of the MASTL-PP2A axis in breast cancer cells. The MKI-2 treatment showed phenocopies with MASTL-null oocyte in mouse oocytes, which were used as a model to validate MKI-2 activity. Therefore, our study provided a new potent and selective MASTL inhibitor MKI-2 targeting the oncogenic MAST-PP2A axis in breast cancer cells.